A Study on Performance and Emission Characteristics of Direct Injection Naturtal Gas Engine - Vu, Minh Hieu; Ho, Huu Chan; Le, Van Cong; Park, Chan Woo; Tran, Dang Quoc (JST: Engineering And Technology For Sustainable Development, 2022)
Natural gas is well known as a promising alternative fuel for internal combustion engine. In this study, a numerical model was built based on the experimental CNG converted engine. Direct injection and port fuel injection method was operated in the model on the same condition such as design parameter, engine speed, compression ratio. The effect of injection method on engine performance and emission characteristics were compared. The mixing and burning properties were also investigated to have further insight about the fuel injection effects. The results have illustrated that the injection strategy had clearly effects on the mixing and combustion process. Due to the better mixture, the direct injection engine has showed the obviously improvement on the emission as well as engine performance. All these results have provided the data and theory to improve the engine performance for the development of the direct injection system for the engine using CNG.